Dismantle Ableism - Khan, Eman (Stimulus: A Medical Humanities Journal, 2023)
This is a painting of a Disabled person pointing their cane at the sky while lightning shoots out of it. It is representative of the resilience of the Disability community in our fight to dismantle ableism. Disability justice involves many layers, as shown by the text surrounding "Dismantle ableism," such as accessibility, self-advocacy, better media representation, and acknowledgement of ableism's intersections with racism, sexism, cissexism, heterosexism.